2019
DOI: 10.4314/sokjvs.v16i4.9
|View full text |Cite
|
Sign up to set email alerts
|

Haematological and biochemical parameters of clinically dehydrated and euhydrated dogs

Abstract: Dehydration results in alterations in haematological and biochemical parameters of dogs. The aim of this study was to determine the haematological and biochemical parameters of clinically dehydrated and euhydrated dogs. A total of 109 samples obtained from different breeds of dogs were used for this study. The degrees/grades of dehydration of each dog were recorded and the dogs were grouped as follows based on their degrees of dehydration: A; euhydrated, B; mildly dehydrated, C; moderately dehydrated and D; se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…Non-significant elevation in packed cell volume (PCV) in association with significant elevation in mean corpuscular volume (MCV) were recorded in dehydrated dogs, the finding of this work were consistent with other reports P value ≤0.05 is considered significant [15] where there was no significant difference in PCV between euhydrated dogs and severely dehydrated one. Meanwhile, significantly higher MCV values was observed between this groups and these findings were attributed to dehydration ratio.…”
Section: Resultssupporting
confidence: 92%
“…Non-significant elevation in packed cell volume (PCV) in association with significant elevation in mean corpuscular volume (MCV) were recorded in dehydrated dogs, the finding of this work were consistent with other reports P value ≤0.05 is considered significant [15] where there was no significant difference in PCV between euhydrated dogs and severely dehydrated one. Meanwhile, significantly higher MCV values was observed between this groups and these findings were attributed to dehydration ratio.…”
Section: Resultssupporting
confidence: 92%
“…In addition, dehydration could have contributed to SDMA changes. Indeed, if dehydration results in a prerenal azotemia reflecting a reduction in the glomerular filtration rate, then SDMA should also increase, along with serum albumin, total protein, urea, and creatinine concentrations [ 48 ]. In a study that included different types of human hematological malignancies, asymmetrical dimethylated arginine but not SDMA was shown to have significantly increased the concentration in the population with malignancies compared with the control group [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown a strong association between emaciation and anemia (Igbokwe et al, 2012), who found almost 37% of sampled emaciated animals to have anemia and even in nonemaciated animals, so the results from the present study, where no animal (including emaciated) had anemia (PCV below 24%) was a deviation. This discrepancy may be due to various degrees of dehydration in sampled animals which confounded the detection of anemia (Atata et al, 2018).…”
Section: Discussionmentioning
confidence: 99%